PENGELOLAAN PASAR TRADISIONAL BERBASIS MUSYAWARAH UNTUK MUFAKAT - Siti Fatimah Nurhayati (Benefit: Jurnal Manajemen dan Bisnis, 2014)
A traditional market certainly differs from modern retail market. Therefore, managementof traditional market is not similar with that of modern one. Because traditional market has uniquecharacteristics that the modern one has not. Recently, growth of traditional market is much leftbehind quantitatively and qualitatively by the modern, while existence of traditional market isperceived as still needed by people. The article aims to discuss ways of managing traditionalmarket in order to produce win-win solutions for all related parties, namely, consumers are satisfied,traders have better earnings, and local government can enhance its income from local resource. It isexpected, therefore, traditional market can survive from competition, and well-developed. Actually,traditional market has good enough potency in developing local economic.